Teknik Pembibitan Tanaman Kemiri (Aleurites moluccana L.) Di UPTD BSPTH Dinas Kehutanan Provinsi Sumatera Barat - Annisa Fauziah; Violita Violita; Mika Lestaria (GLOBAL SCIENTS PUBLISHER, 2026)
A professional internship was conducted at the Forest Plant Certification and Seedling Center (UPTD BSPTH) of West Sumatra Provincial Forestry Service from January 5 to February 18, 2026, focusing on the seedling techniques of candlenut (Aleurites moluccana L.). This article aims to describe the seedling stages applied at UPTD BSPTH, including seed selection, pre-germination treatment, sowing, germination observation, transplanting to polybags, and seedling maintenance. The method used was participative observation and direct field observation. Results showed that the nursery medium consisted of a mixture of mineral soil, fine sand, organic compost, and rice husks. Mechanical scarification treatment was effective in increasing germination percentage. Seeds germinating in the center of the seedbed tended to sprout earlier due to more even moisture and temperature distribution. The produced candlenut seedlings showed good quality, characterized by strong taproots, erect dark-green stems, and normally developed leaves. The seedling technique applied at UPTD BSPTH is in accordance with the principles of forest plant nursery management, producing seedlings suitable for land rehabilitation and reforestation programs in West Sumatra.